What next in cervical cancer screening? - Sehnal, B; Sláma, J (Ceska gynekologie, 2020)
INTRODUCTION: The main aim of organized national cervical cancer screening programs is to decrease incidence and mortality of this malignancy. A total of 770 cases of cervical cancer and 354 deaths from the disease were noticed in the Czech Republic in 2017 which means the incidence 14,5 new cases per 100 000 women. The Czech national cervical cancer screening program is based on cytology (Pap smear) testing in asymptomatic women once a year. OBJECTIVE: To provide an overview of new possibilities and potential tools in cervical cancer screening worldwide and in the Czech Republic. SETTING: Gynecologic Oncology Center, Department of Gynecology and Obstetrics, Hospital Na Bulovce and 1st Medical School of Charles University, Prague; Gynecologic Oncology Center, Department of Gynecology and Obstetrics, General Faculty Hospital and 1st Medical School of Charles University, Prague. METHODS: For this review, we have used the results of studies, review articles, and guidelines of national cervical cancer screening programs published in English. We summarize the current knowledge of molecular genetic methods being applied in the screening of cervical carcinoma. CONCLUSION: The knowledge that persistent human papillomavirus (HPV) infection is the main cause of cervical cancer has resulted in the development of new possibilities of cervical cancer screening worldwide. HPV testing use for cervical cancer screening is now a reality with a quite lot of countries. Nevertheless, HPV testing is mainly used in the stratification of patients with unclear results of a cytological (PAP smear) result in the Czech Republic. While there is a wide and growing consensus that HPV molecular testing is the most accurate and cost-effective method of primary screening, there is a comparative lack of consensus regarding the optimal stratification of patients with proven HPV infections. Biomarkers, such a p16/Ki67 dual immunostaining, a methylation of viral DNA, a detection of E6/E7 mRNA, and others have been proposed for triage of HPV positive women. New possibilities and approaches in strategy of cervical cancer screening are discussed.
Keywords: Pregnancy; Humans; mass screening; p16/Ki67; Female; screening; nádory děložního čípku; Early Detection of Cancer; lidé; cervical uterine cancer; Methylation; časná detekce nádoru; Papillomaviridae; Papillomavirus Infections; cervical cancer; ženské pohlaví; HPV test; těhotenství; Czech Republic; Mass Screening; E6/E7 mRNA; infekce papilomavirem; Uterine Cervical Neoplasms; plošný screening; Česká republika; molecular methods